Head Injuries at the Emergency Department of a University Hospital - Henriksson, Thérèse; Kjellberg, Jacob; Shakya, Yogendra; Kurlberg, Göran (Journal of Institute of Medicine Nepal, 2020)
Introduction Traumatic head injuries constitute a major cause of morbidity and mortality worldwide. The developing world is particularly affected due to a high prevalence of risk factors and difficulties in enforcing preventive efforts. This study was carried out at the Emergency Department (ED), Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal – where head injuries account for five per cent of all emergency visits. The aim was to describe demographics, cause of trauma, type of injury, and severity according to the Glasgow Coma Scale (GCS), as well as the outcome of emergency attendance in patients seeking medical care for traumatic head injuries. Auxiliary aims were to study correlations between age, cause of trauma and injury severity.MethodsData from 577 cases of head injuries from June to October 2019 were collected retrospectively.ResultsTraumatic head injuries accounted for 5.2 % of all emergency visits. The median age was 23 years. Patients were predominantly male. Superficial injuries and concussions were the most common. Most injuries were mild (94.4 %, GCS 13–15) and caused by falls (51.3 %) or road traffic accidents (19.1 %). Fall accidents and mild injuries had the lowest median age. Patients from outside Kathmandu Valley constituted 44.9 % of the cases. Only 12.1 % of the patients were admitted to the hospital.ConclusionCommonest head injuries are mild and superficial; and are caused by falls and road traffic accidents. Most head injury patients are children.